Hubungan antara Bayi Berat Lahir Rendah dan Lingkar Lengan Atas - Bobby Ibrahim Arbie; Diana Wulandari; I Nyoman Adi Wacika; Mendy Audian Paramita; Andiani Andiani (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2022)
Low Birth Weight (LBW) is defined as a baby's weight at birth of less than 2,500 grams. LBW can also have a long-term impact on the baby's life in the future, such as experiencing mental and physical disorders at the age of infant growth and development. Measurement of upper arm circumference (MUAC) can be used as an assessment of the nutritional status of pregnant women, including chronic energy deficiency (CED) if the size of the upper arm circumference (MUAC) is less than 23.5 cm in pregnant women. Maternal nutrition during pregnancy plays an important role, because the status of chronic energy deficiency (CED) before pregnancy affects fetal growth. Seeing from the description that has been described above, the researchers are interested in conducting research related to the relationship between low birth weight babies and upper arm circumference in Kutogirang Village, Ngoro Community Health Center, Mojokerto Regency. This research is an observational quantitative research using a cross sectional research design. The data analysis used in this research is Chi-Square. There is a significant relationship between low birth weight babies and maternal upper arm circumference in Kutogirang Village, the working area of the Ngoro Health Center, Mojokerto Regency in 2020. From the OR data it can be concluded that mothers with MUAC < 23.5 cm have a 19.33 times higher risk of having children with LBW than mothers with normal MUAC.